2015
DOI: 10.1021/jacs.5b06120
|View full text |Cite
|
Sign up to set email alerts
|

A Nearly Ideal One-Dimensional S = 5/2 Antiferromagnet FeF3(4,4′-bpy) (4,4′-bpy =4,4′-bipyridyl) with Strong Intrachain Interactions

Abstract: An ideal one-dimensional (1D) magnet is expected to show exotic quantum phenomena. For compounds with larger S (S = 3/2, 2, 5/2, ...), however, a small interchain interaction J' tends to drive a conventional long-range ordered (LRO) state. Here, a new layered structure of FeF3(4,4'-bpy) (4,4'-bpy = 4,4'-bipyridyl) with novel S = 5/2 (Fe(3+)) chains has been hydrothermally synthesized by using 4,4'-bpy to separate chains. The temperature-dependent susceptibility exhibits a broad maximum at high as 164 K, sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 54 publications
3
18
0
Order By: Relevance
“…The inorganic ionic groups such as [ [10][11][12]. Also, the fluorine plays an important role in the regulation of structure, magnetic and optical properties [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inorganic ionic groups such as [ [10][11][12]. Also, the fluorine plays an important role in the regulation of structure, magnetic and optical properties [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is recently reported that the organic molecule could be more efficient to separate spin chains with negligible interchain interaction J΄ for experimentally realizing the nearly ideal 1D S = 5/2 antiferromagnet (4,4΄-bpy)FeF 3 (4,4΄-bpy = 4,4΄-bipyridyl) [15].…”
Section: Introductionmentioning
confidence: 99%
“…The μ eff of the sample with x = 0i sc lose to the theoreticals pin-only moment of Fe 3 + (5.92 μB) indicating the domination of super-exchange antiferromagnetic interactions (Fe 3 + -O 2À -Fe 3 + ). [23,36] The lower value of μ eff at x = 0.3 could imply the presence of Fe 4 + or Fe 2 + increase as both cations have as maller magnetic moment (4.9 μB). In this work, an increase of Fe 4 + is more reasonable as it is confirmed by absorption spectroscopy measurements.T he change of θ and μ eff value with niobium doping may be attributed to the enhancement of double exchange interactions (Fe 3 + -O 2À -Fe 4 + ).…”
Section: Resultsmentioning
confidence: 99%
“…Nonlinear optical (NLO) materials have attracted considerable attention due to their potential application in developing new light sources by frequency‐conversion technology [1–27] . In the UV and visible regions, NLO materials have made significant progress.…”
Section: Introductionmentioning
confidence: 99%